THE STRUGGLE AGAINST SOVIET RULE IN SURKHANDARYA OASIS AND ITS PECULIARITIES (1925-1933) (Scientific journal of the Fergana State University, 2023)
The article is devoted to the history of the armed movement against the Soviet regime in the Surkhandarya oasis. It analyzes the leaders fighting against the red army, their activities, as well as the dynamics of the armed movement. Also, the policy of struggle of the Soviet power against kurbashi is revealed.